Post-Discharge Needs of Victims of Gun Violence in Chicago: A Qualitative Study. Issue 1 (January 2019) - Patton, Desmond; Sodhi, Aparna; Affinati, Steven; Lee, Jooyoung; Crandall, Marie
The purpose of this study was to understand the post-discharge needs of violently injured patients and their families to improve health outcomes and reduce the impact of gun violence. We recruited 10 patients from the trauma registry of a Midwestern university hospital with a Level 1 Trauma Center (L1TC). After obtaining the informed consent, semi-structured, face-to-face, in-depth interviews were conducted. Discussions focused on post-discharge needs and resources to facilitate the recovery and rehabilitation process, and aid in community reintegration. Interviews were audiotaped and transcribed verbatim. Transcripts were analyzed thematically in stages of open, axial, and selective coding methods. Seven main themes were identified at the hospital and community level. These included the following: (a) feeling stigmatized by hospital personnel, (b) patient–provider communication, (c) feeling discharged too soon, (d) issues in obtaining medicines, (e) challenges with Chicago Police Department, (f) transportation to trauma center for follow-up care, and (g) concerns with returning back to the community. Patients reported the need for mental health counseling for themselves and their family, more follow-up, and help with financial paperwork among others. For the victims of gun violence, there exists a chasm between injury and care, and an even wider one between care and rehabilitation. The findings can inform health care, social workers, and rehabilitation professionals in their efforts to better address the myriad of unmet needs pre- and post-discharge. For trauma centers, the identified needs provide a template for developing an individualized- and community-centered resource pathway to improve outcomes and reduce suffering for this particularly vulnerable subset of patients.